Depth resolution at organic interfaces sputtered by argon gas cluster ions: the effect of energy, angle and cluster size. Issue 19 (7th October 2015) - Seah, M. P.; Spencer, S. J.; Havelund, R.; Gilmore, I. S.; Shard, A. G.
<x xml:space="preserve">Abstract</x> This paper presents, for the first time, the different operating parameters defining the best depth resolution in SIMS organic analysis.